Notas de matemática do ensino médio em 2021: Uma análise empírica, a partir de dados da OBMEP, do uso de internet pelos alunos e do Saeb - Luis Claudio Kubota; Mauricio Benedeti Rosa (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
– The purpose of this study is to develop an empirical analysis of the influence of several variables in the average proficiency of Brazilian High School students in mathematics - measured by Saeb's results. We aim to investigate the contribution of OBMEP - measured by the prizes by school - and the use of internet in the school by the students - an information obtained from School Census. Results indicate that the main positive determinants for Saeb grades are the existence of admission tests and the indicator of socioeconomic status of the school. In the first case, there is a selection bias, whereas the students with better cognitive skills are selected. In the second case, socioeconomic status is a known determinant of student and school performance. On the one hand, the use of internet by students is not associated with specifications regarding Saeb. On the other hand, the coefficients of OBMEP prizes have positive sign and are statistically significant.
Keywords: I21; 330; XOBMEP; Saeb; internet; proficiency; mathematics